A Multi-element Microstrip Antenna for LTE Bands, Wi-Fi and WiMAX Application in Femtocell Network - Zakaria Er-Reguig; Hassan Ammor (IAES Indonesian Section, 2018)
Interference management is the key point in the deployment of ultra-dense networks. Several techniques in physical and data-link layers have been discussed and proposed to provide lower power and better network capacity, while minimizing the cost and complexity of FemtoCell deployment. The applicability of an antenna with microstrip technology that employs multiple elements is developed here for coverage enhancement of FemtoCell network. The antenna proposed in this research has a size of 35 x 35 x 1.58 mm3, it is printed on a commercially available FR4 dielectric substrate and designed for the frequency band from 1.9 GHz to 3.5 GHz. The different results obtained of the studied antenna in the FemtoCell scenario are discussed.